Fault detection aviation pipelines with use of features of the absent-minded sound field - Шкварницька, Т. Ю. (Proceedings of National Aviation University (archive), 2003)
The mathematical analysis of an absent-minded sound field of the pipeline is lead. Calculation of sound pressure in an absent-minded field for the aluminium and steel pipelines is executed. Comparisons of the calculated data with experimental are resulted. Influence of defect on characteristics of an absent-minded sound field of the pipeline is investigated